RESEARCH ON VEHICLE INTELLIGENT FRAGRANCE FLUID SIMULATION AND NOISE REDUCTION (Jixie qiangdu)
The existing miniaturized vehicle intelligent fragrance devices in China generally have problems such as small air volume and high noise,resulting in poor user experience.In view of the above problems,firstly,a miniaturized vehicle intelligent fragrance device based on Catia software was designed.Secondly,based on the computational fluid dynamics(CFD)method,the flow field simulation analysis of the vehicle intelligent fragrance device was carried out,and the air volume was optimized by improving the air path and the size of the air outlet.The optimized air volume is 1.2 m3/h,which is 16.7% higher than that before optimization,which verifies the feasibility of the optimization method.Finally,based on Siemens Simcenter Testlab system,the noise reduction of the vehicle intelligent fragrance devices was studied.The scheme of isolating vibration source and adjusting motor subdivision was proposed to reduce noise.The experimental results show that the noise of the whole machine is reduced by 5.61 dB(A),which verifies the effectiveness of the noise reduction method.The structural design method,air volume optimization method and noise reduction technology scheme provide a strong reference for product development in the field of vehicle electronics.